Aerodynamic characteristics of wind disaster area in High Tatra Mts - HURTALOVÁ, Taťjana; OSTROŽLÍK, Marián; MATEJKA, František (Contributions to Geophysics and Geodesy, 2008)
The 19 November 2004 windstorm caused significant forest damage in High Tatra Mts. when about 12000 ha of forest stand was totally destroyed during this devastating windstorm effect. The vegetation type was dramatically changed when closed forest stands with age of 40–110 years were replaced by low vegetation. One part of this locality was also fire-stricken in July 2005. The extensive research and monitoring of meteorological and microclimatological characteristics is carried out on 4 windstorm-stricken sites. In this contribution an analysis of the airflow and wind speed profiles measured above one of them, the research fired site (FIRE site, φ = 49° 18′ N, λ = 20° 12′ E), is presented. This site is situated at a slope of 5–10% with SE orientation in the height 1000–1200 m a.s.l. The analysed wind direction and wind speed profiles were measured continuously by the wind speed and direction sensor WindSonic on 4 m high measured stand in four levels: 0.5, 1.0, 2.0, and 4.0 m from May 15 to July 17, 2007. The roughness length and aerodynamic resistance values were determined using this wind speed profile analysis. Dependencies of aerodynamic resistance on the roughness length and wind speed were analysed.